Supplementation of kefir ameliorates azoxymethane/dextran sulfate sodium induced colorectal cancer by modulating the gut microbiota. Issue 22 (1st November 2021) - Zeng, Xuejun; Jia, Hang; Zhang, Xiao; Wang, Xin; Wang, Zhouli; Gao, Zhenpeng; Yuan, Yahong; Yue, Tianli
Abstract : Supplementation of kefir alleviated AOM/DSS induced colorectal cancer by modulating the gut bacterial and fungal microbiota. Abstract : The aim of this study was to investigate the efficacy of kefir on colorectal cancer (CRC) via regulating the microbiota structure in the colon using the azoxymethane/dextran sulfate sodium (AOM/DSS) induced CRC mouse model. Mice in the treatment group were orally administered with milk or kefir. The gut microbiota composition was assessed by internally transcribed spacer 2 (ITS2) and 16S rRNA high-throughput sequencing. Furthermore, the biomarkers associated with the gut barrier, inflammation, and cell proliferation regulators were evaluated. The results indicated that the size and the amount of tumor were decreased and the immunity regulators (TNF-α, IL-6, and IL-17a) and oncocyte proliferation indicator (Ki67, NF-κB, and β-catenin) were all decreased. Increased short chain fatty acids (SCFAs) lowered the pH in the colon and helped enhance the intestinal barrier. The Firmicutes / Bacteroidetes ratio and Ascomycota / Basidiomycota ratio were decreased at the phylum level; the relative abundance of probiotics was increased and the pathogenic bacterium ( Clostridium sensu stricto, Aspergillus and Talaromyces ) were decreased after supplementation of kefir. Consequently, kefir could regulate the gut microbiota composition and ameliorate AOM/DSS induced colorectal cancer.